The cation-deficient Ruddlesden-Popper oxysulfide Y2Ti2O5S2 as a layered sulfide: topotactic potassium intercalation to form KY2Ti2O5S2. - Rutt, O; Hill, T; Gál, Z; Hayward, M; Clarke, S (2003)
Potassium intercalation into the cation-deficient n = 2 Ruddlesden-Popper oxysulfide Y(2)Ti(2)O(5)S(2) to form KY(2)Ti(2)O(5)S(2) has been carried out by reaction of the oxysulfide with potassium vapor in sealed metal tubes at 400 degrees C, potassium naphthalide in THF at 50 degrees C, or potassium in liquid ammonia at temperatures as low as -78 degrees C. Insertion of potassium is topotactic, and although a site 12-coordinate by oxide ions is vacant in the perovskite-type oxide slabs of the structure, potassium is too large to enter this site via the 4-coordinate window, and instead enters the rock-salt-type sulfide layers of the structure which necessitates a 30% increase in the lattice parameter c normal to the layers. In contrast with one of the sodium intercalates of Y(2)Ti(2)O(5)S(2) (beta-NaY(2)Ti(2)O(5)S(2)) in which sodium occupies a tetrahedral site in the sulfide layers, potassium favors an 8-coordinate site which necessitates a relative translation of adjacent oxide slabs. KY(2)Ti(2)O(5)S(2) is tetragonal: P4/mmm, a = 3.71563(4) A, c = 14.8682(2) A (at 298 K), Z = 1. Although the resistivity (3.4(1) x 10(3) Omega cm) is larger than would be expected for a metal, temperature independent paramagnetism dominates the magnetic susceptibility, and the material is electronically very similar to the analogous sodium intercalate beta-NaY(2)Ti(2)O(5)S(2) which features reduced-titanium-containing oxide layers of very similar geometry and electron count.